THE ANATOMY OF A CRIME: THE UNFINISHED CASE OF THE BOOK THEFT FROM VILNIUS UNIVERSITY LIBRARYIN THE 19TH CENTURY - PACEVIČIUS, ARVYDAS (Knygotyra, 2015)
Vilniaus universiteto Bibliotekininkystės ir informacijos mokslų institutas, Universiteto g. 3, LT-01513 Vilnius, Lietuva El. paštas: arvydas.pacevicius@kf.vu.lt